2022
DOI: 10.3389/fphar.2022.994643
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the roles of Autophagy in OSCC: A renewed perspective from mechanisms to potential applications

Abstract: Oral squamous cell carcinoma (OSCC) is associated with a low survival rate and a high disability rate, making it a serious health burden, particularly in Southeast Asian countries. Therefore, improvements in the diagnosis, treatment, and prognosis prediction of OSCC are highly warranted. Autophagy has a significant impact on cancer development. Studies on autophagy in various human cancers have made outstanding contributions; however, the relationship between autophagy and OSCC remains to be explored. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“… 45 Although it has been proven that suppressing autophagy can augment the treatment effects of various cancer therapies, 46 the induction of autophagic cell death can efficiently kill certain types of cancer cells, and is well recognized as a promising strategy to treat various types of cancers including OSCCs. 10 , 43 , 44 , 46 It is not surprising that biguanide drugs are expected to trigger autophagy since both metformin and phenformin induce AMPK activation which results in the inhibition of mTOR, one of the major regulators of autophagy. 47 Metformin has been reported to promote autophagic cell death to play an anti-tumor function in many types of cancer cells, including gastric cancer cells, ovarian cancer SKOV3 cells, and hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 Although it has been proven that suppressing autophagy can augment the treatment effects of various cancer therapies, 46 the induction of autophagic cell death can efficiently kill certain types of cancer cells, and is well recognized as a promising strategy to treat various types of cancers including OSCCs. 10 , 43 , 44 , 46 It is not surprising that biguanide drugs are expected to trigger autophagy since both metformin and phenformin induce AMPK activation which results in the inhibition of mTOR, one of the major regulators of autophagy. 47 Metformin has been reported to promote autophagic cell death to play an anti-tumor function in many types of cancer cells, including gastric cancer cells, ovarian cancer SKOV3 cells, and hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“… 13 The promotion of autophagic cell death has been shown to suppress the growth of various types of tumor cells including OSCC cells. 9 , 10 , 14 For example, ursolic acid has been reported to promote apoptosis and autophagy by inhibiting the AKT/mTOR/NF-κB pathway and significantly inhibits the migration and invasion of the OSCC cell lines CA-922 and SCC-2095. 15 Several studies have reported low expression levels of Beclin-1, an indicator of autophagy, in OSCC specimens, 16 18 and silencing Beclin-1 significantly promotes OSCC migration, proliferation and invasion while inhibiting apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the roles of autophagy in OSCC remain controversial. While autophagy enhances the stemness and malignancy of OSCC cells, it can also promote their apoptosis (52). Overall, the role of autophagy in OPMDs and OSCC and whether abnormal DNA methylation leads to abnormal functioning of autophagy-related genes warrants further study.…”
Section: Current Studies On Dmr-related Genesmentioning
confidence: 98%
“…Autophagy serves as a recycling program to maintain ATP production and cell homeostasis. Studies have revealed that autophagy keeps cancer stem cells viable, promotes EMT signaling and thus, OSCC [28]. However, there is also contradictory evidence indicating that autophagy may also inhibit apoptosis, migration, and invasion of OSCC cells.…”
Section: Rage Independent Mechanismsmentioning
confidence: 99%
“…However, there is also contradictory evidence indicating that autophagy may also inhibit apoptosis, migration, and invasion of OSCC cells. These contradictory data have been attributed to the different stages of OSCC used in different studies [28]. HMGB1 has been shown to increase pro-survival autophagy through binding to Beclin-1, a key regulator of autophagy [7] and inhibit apoptosis, in several clinical settings, including OSCC.…”
Section: Rage Independent Mechanismsmentioning
confidence: 99%